2020
DOI: 10.3390/molecules25194550
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization and Antioxidant Activities of Kelp Phlorotannin Nanoparticles

Abstract: Phlorotannins are a group of major polyphenol secondary metabolites found only in brown algae and are known for their bioactivities and multiple health benefits. However, they can be oxidized due to external factors and their bioavailability is low due to their low water solubility. In this study, the potential of utilizing nanoencapsulation with polyvinylpyrrolidone (PVP) to improve various activities of phlorotannins was explored. Phlorotannins encapsulated by PVP nanoparticles (PPNPS) with different loading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…In our study, the FTIR spectra also revealed that ACM was incorporated into HPBCD with PVPK30, and a certain degree of interaction between ACM and carriers, for the stability of amorphous ACM, is important for forming a novel nanoparticle formulation ( Figure 4 ). Similar findings were also found for kelp phlorotannin [ 33 ], indomethacin [ 34 ], and fullerenes [ 35 ]. These changes in physicochemical characteristics could elucidate the mechanism of water-solubility improvement.…”
Section: Discussionsupporting
confidence: 79%
“…In our study, the FTIR spectra also revealed that ACM was incorporated into HPBCD with PVPK30, and a certain degree of interaction between ACM and carriers, for the stability of amorphous ACM, is important for forming a novel nanoparticle formulation ( Figure 4 ). Similar findings were also found for kelp phlorotannin [ 33 ], indomethacin [ 34 ], and fullerenes [ 35 ]. These changes in physicochemical characteristics could elucidate the mechanism of water-solubility improvement.…”
Section: Discussionsupporting
confidence: 79%
“…Last by not least, phlorotannins are strong natural antioxidants [55][56][57][58][59][60]. Dieckol can suppress UV-B radiation induced photo-oxidative stress in human fibroblast cell line and reduce cell damage [55]; diphlorethohydroxycarmalol (DPHC) isolated from I. okamurae can scavenge UV-B radiation induced ROS in human fibroblast cells [57]; and dieckol can reduce cell damage induced by UV-B radiation both in vitro (HaCaT cells) [61] and in vivo (zebra fish) [59]. Phlorotannins can also potentially be used as functional ingredients in skin care products to offer protection against photo-induced skin damages.…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenols' low bioavailability is mainly due to their low absorption in the human gastrointestinal (GI) tract following consumption and their extensive biotransformation within the gut, which may lead to their rapid clearance from the body (Figure 1 [62]). To improve the bioavailability of phlorotannins, nano-sized delivery systems have been investigated [26,61,[63][64][65][66][67][68][69][70]. Figure 2 showed a schematic representation of examples of these systems [71].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations